2007
DOI: 10.1021/bi701370e
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Substrate Binding Mode to the Active Site Iron of (S)-2-Hydroxypropylphosphonic Acid Epoxidase Using 17O-Enriched Substrates and Substrate Analogues

Abstract: Abstract(S)-2-hydroxypropylphosphonic acid epoxidase (HppE) is an O 2 -dependent, nonheme Fe(II)-containing oxidase that converts (S)-2-hydroxypropylphosphonic acid ((S)-HPP) to the regio-and enantiomerically specific epoxide, fosfomycin. Use of (R)-2-hydroxypropylphosphonic acid ((R)-HPP) yields the 2-keto-adduct rather than the epoxide. Here we report the chemical synthesis of a range of HPP analogs designed to probe the basis for this specificity. In past studies, NO has been used as an O 2 surrogate to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 35 publications
3
31
0
Order By: Relevance
“…However, the heterogeneity observed in the EPR spectrum of the ternary complex of Ps -HppE suggests that substrate binding to the active site Fe(II) ion in two different conformations. Our recent isotope labeling study showed that the uniform EPR signal observed for the ternary complex of Sw -HppE is a result of substrate coordination to the Fe(II) ion in a bidentate fashion (39). This same species is also observed with Ps -HppE, although it represents only 30% of the total iron.…”
Section: Resultsmentioning
confidence: 99%
“…However, the heterogeneity observed in the EPR spectrum of the ternary complex of Ps -HppE suggests that substrate binding to the active site Fe(II) ion in two different conformations. Our recent isotope labeling study showed that the uniform EPR signal observed for the ternary complex of Sw -HppE is a result of substrate coordination to the Fe(II) ion in a bidentate fashion (39). This same species is also observed with Ps -HppE, although it represents only 30% of the total iron.…”
Section: Resultsmentioning
confidence: 99%
“…207,208 EPR analysis of anaerobic, enzyme-bound Fe II -NO complexes in the presence and absence of ( S )-HPP and various substrate analogues confirmed that both the C2-OH and phosphonate functional groups of ( S )-HPP were required for bidentate binding. 204,215 The direct coordination of the negatively charged phosphonate group to the iron center in this binding mode likely helps activate Fe II towards O 2 binding and may also assist in the formation of higher iron oxidation states for substrate oxidation. 216 Overall, the crystallographic and EPR studies shed light on how HppE is able to bind HPP, prime iron for O 2 binding, and shield reactive intermediates from solvent.…”
Section: Epoxide Biosynthesismentioning
confidence: 99%
“…Liu and coworkers reconstituted the activity of the HPP epoxidase (HppE) in vitro [38] and showed that the enzyme requires Fe(II), O 2 , an electron carrier (either a general reductase or catalytic amounts of FMN) and NADH as reductant, but not α-ketoglutarate. Subsequent spectroscopic, mechanistic, and structural investigations established that the enzyme is a mononuclear non-heme-iron-dependent oxidase [22,3941]. …”
Section: -Hydroxypropylphosphonate Epoxidasementioning
confidence: 99%
“…The latter binding mode is associated with a more closed conformation that appears to shield the active site from solvent and may help protect reactive intermediates. Further support for productive bidentate HPP binding has been provided by EPR studies with 17 O-labeled substrate and using NO as mimic of oxygen [41]. The bidentate binding of HPP resembles the binding geometry of α-ketoglutarate (α-KG) in other members of the cupin family [42,43], and analogously the bidentate binding by HPP may serve to facilitate the normally unfavorable reaction of ferrous iron with molecular oxygen [22].…”
Section: -Hydroxypropylphosphonate Epoxidasementioning
confidence: 99%